The Presidents and the Poor : America Battles Poverty, 1964-2017 - McAndrews, Lawrence J. (Lawrence John) (Book collections on Project MUSE., 2018)
"Ever since Lyndon Johnson launched his "War on Poverty," each presidential administration has engaged in a unique effort to help impoverished Americans. Though every president inherited the remnants of his predecessors' policies, each sought to make his own mark and secure his own place in history. The combatants changed, the terrain shifted, the losses mounted, and the victories faded. Johnson (inspired by Kennedy) may have devised the initial strategy to conduct the campaign, but subsequent presidents amplified, altered, and even overturned it. The Presidents and the Poor is an account of honorable intentions, innovative ideas, colossal sums of money, and a vast expansion of government. In the end, however, it is a tale of how nine presidents did not do too much, but too little, to help those on the lowest rungs of American society. Democrats Lyndon Johnson, Jimmy Carter, Bill Clinton, and Barack Obama were never fully able to commit the resources that they believed were necessary to defeat poverty. Republicans Richard Nixon, Gerald Ford, Ronald Reagan, George H.W. Bush, and George W. Bush could never completely fulfill their alternate visions of LBJ's war. Some--notably Johnson, Nixon, Reagan, and Clinton--did better than others in making inroads against poverty, but all fell short of their goals. And impoverished Americans were left to wonder what might have been, if only their presidents had fought to win against an unyielding enemy"--